2018
DOI: 10.1186/s12895-018-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistence rates and medical costs of biological therapies for psoriasis treatment in Japan: a real-world data study using a claims database

Abstract: BackgroundBiological therapies (BTs) including infliximab (IFX), adalimumab (ADL), secukinumab (SCK) and ustekinumab (UST) are approved in Japan for the treatment of psoriasis. Although the persistence rates and medical costs of BTs treatment have been investigated in multiple foreign studies in recent years, few such studies have been conducted in Japan and the differences between patients who adhered to treatment and those who did not have not been reported. This study is aimed at investigating the persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 25 publications
7
69
0
1
Order By: Relevance
“…Because the treatment choice scenarios were prepared assuming biologic treatments for moderate to severe psoriasis, it might have been difficult for some participants to personally relate to the selection based on their past experience. However, the study showed similar trends consistent with previous studies presenting greater preference for dosing convenience, higher prescription rate of treatments with longer dosing frequencies in females, more concern about severe adverse event occurrence in the elderly patients, and lower importance of co‐payment or cost in patients currently treated with biologics . These results may partially support the external validity of the study.…”
Section: Discussionsupporting
confidence: 88%
“…Because the treatment choice scenarios were prepared assuming biologic treatments for moderate to severe psoriasis, it might have been difficult for some participants to personally relate to the selection based on their past experience. However, the study showed similar trends consistent with previous studies presenting greater preference for dosing convenience, higher prescription rate of treatments with longer dosing frequencies in females, more concern about severe adverse event occurrence in the elderly patients, and lower importance of co‐payment or cost in patients currently treated with biologics . These results may partially support the external validity of the study.…”
Section: Discussionsupporting
confidence: 88%
“…1a). This definition of persistence was consistent with that employed in other claims data-based studies of RA [10, 26] and other indications [27, 28].
Fig.
…”
Section: Methodssupporting
confidence: 87%
“…[8][9][10] Among claims-based studies, some use a permissible gap of 150 days for ustekinumab (which has a 12-week maintenance dosing interval) and 90 days for all other drugs (which are dispensed every 4 weeks during the maintenance period). 11,12 However, this method is not responsive to the differences between induction and maintenance dosing or to dose escalation. Other studies completely exclude the induction period from their analysis, then apply a permissible gap of 28 days for etanercept, 56 days for adalimumab, and 126 days for ustekinumab on the basis of expert opinion.…”
mentioning
confidence: 99%